Industrial Relations in Bali’s Tourism Industry: Challenges and Implications for Employee Welfare - Dwi Ayu Putri Pradyandari; R Tri Priyono Budi Santosa (Bali Tourism Journal, 2026)
Tourism is one of the most strategic sectors supporting economic growth, employment creation, and regional development in Bali, Indonesia. As a labor-intensive industry, tourism performance is highly dependent on the quality of industrial relations between employers, employees, labor unions, and government institutions. Despite its substantial contribution to the regional economy, Bali’s tourism industry continues to face persistent industrial relations challenges that negatively affect employee welfare. This conceptual article aims to examine industrial relations issues in Bali’s tourism industry and analyze their implications for employee welfare. The study adopts a qualitative, literature-based approach by reviewing academic journal articles, labor regulations, and international reports related to industrial relations, tourism employment, and employee welfare, particularly within the context of Indonesia and Southeast Asia. The review identifies key challenges, including wage inequality, employment insecurity due to the dominance of contract-based employment, limited labor protection, and weak employee participation in organizational decision-making. The findings suggest that fragile industrial relations practices reduce employee welfare in terms of income stability, job satisfaction, psychological well-being, and access to social security. Moreover, weak industrial relations also undermine service quality and organizational performance, which are critical for competitiveness in the tourism sector. Strengthening industrial relations through fair employment practices, transparent communication, effective social dialogue, and consistent government supervision is therefore essential to enhance employee welfare and support sustainable tourism development in Bali.